Indications for nerve-sparing surgery for radical prostatectomy: Results from a single-center study - Zhu, Zaisheng; Zhu, Yiyi; Xiao, Yunyuan; Hu, Shengye (Frontiers in Oncology, 2022)
Purpose: To explore the clinical indications of using the nerve-sparing technique in radical prostatectomy. Patients and methods: We retrospectively analyzed the clinical and pathological data of 101 patients who underwent radical prostatectomy (RP) at our institution. 25 patients performed open surgery and 76 patients operated on laparoscopic surgery. The biochemical recurrence (BCR) rate was analyzed by the method of Kaplan–Meier. The distance between the ipsilateral neurovascular bundles (NVBs) and foci of prostate tumor (N-T distance) was measured in postoperative specimens. We defined the N-T distance＞2mm as the threshold to perform nerve-sparing (NS) in RP. Through logistic regression analysis, we determined the preoperative clinical indications for the nerve-sparing technique in RP. Results: The average BCR-free survival time was 53.2 months in these 101 patients with RP, with the 3 and 5-year BCR-free rates being 87.9% and 85.8%, respectively. The N-T distance was measured in 184 prostate sides from postoperative specimens of 101 patients. Univariate analysis showed that percent of side-specific biopsy cores with cancer (≥ 1/3), maximum tumor length in biopsy core (≥ 5mm), average percent involvement of each positive core (≥ 50%), PI-RADS score, and prostate MP-MRI imaging (extra-capsular extension) were associated with the N-T distance (p < 0.003). Furthermore, the percent of side-specific biopsy cores with cancer (≥1/3) (OR = 4.11, p ＝ 0.0047) and prostate MP-MRI imaging (extra-capsular extension) (OR = 3.92, p ＝ 0.0061) were found to be statistically significant independent predictors of the N-T distance in multivariate analysis. Conclusions: The clinical indications of nerve-sparing RP were <1/3 side-specific biopsy cores with cancer and no extra-capsular extension by prostate MP-MRI examination.